Peningkatan Motivasi Belajar Peserta Didik dengan Menerapkan Model Pembelajaran Kooperatif Tipe Make A Match pada Mata Pelajaran Ekonomi Kelas XII IPS 2 SMAN 13 Pekanbaru - Neneng Yuyu Rohana (Journal on Education, 2022)
This study was structured with the aim of knowing an increase in students' learning motivation by applying the Make A-Match type cooperative model for class XII IPS 2 SMA Negeri 13 Pekanbaru in economics learning. This type of research is Classroom Action Research (CAR), where the teacher is the executor of learning while the researcher is the observer. The research design used the Arikunto model. This research was conducted in the odd semester of the 2019/2020 school year, namely July 2019. The subjects of this study were class XII IPS 2 students consisting of 28 students. The object of research is the learning motivation of students. Data collection techniques using observation and documentation. Data were analyzed descriptively and presented in the form of tables and graphs. The results showed that there was an increase in students' learning motivation in cycle I, which was an average of 73% (good) and learning motivation in cycle II, which was an average of 86% (very good). This is an increase of 13%. Thus the use of the Make A-Match cooperative learning model in accounting lessons on Accounting as an Information System can increase the learning motivation of students in class XII IPS 2 SMAN 13 Pekanbaru.